Generation Z Preferences in Financial Risk Management (A Comparative Study of Emergency Funds and Sharia Insurance) - Annisa Ayu Kusuma; Tuti Anggraini; Andri Soemitra (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This study aims to examine Generation Z's preferences in choosing financial risk management strategies, with a focus on comparing the use of emergency funds and Islamic insurance. Generation Z, known for their adaptability to technology and information, faces complex financial challenges amidst global economic uncertainty. Using a descriptive qualitative approach, data were obtained from in-depth interviews with a number of Generation Z respondents in urban areas. The results show that although the majority of respondents understand the importance of emergency funds as a form of short-term protection, there is increasing interest in Islamic insurance as an alternative that is considered more systematic and in line with religious values. The main factors influencing this preference include the level of financial literacy, trust in Islamic financial institutions, and perceptions of long-term benefits. These findings are expected to contribute to the development of more relevant financial education strategies for the younger generation. In Press, Journal Pre-proof. Journal pre-proofs are Articles in Press that have been peer reviewed and accepted for publication by the Editorial Board of this publication. They have undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but are not yet definitive versions of record. These versions will undergo additional copyediting, typesetting, and review, and may not yet have full functionality. For example, supplementary files may still need to be added, links to references may not resolve yet, etc. The text could still change before final publication. Although journal preprints do not yet include all bibliographic details, they can be cited using the year of online publication and the DOI, as follows: author(s), article title, Publication (year), DOI. Please consult the journal’s reference style for the exact appearance of these elements, abbreviation of journal names, and use of punctuation. When the final article is assigned to a volume/issue of the publication, the Article in Press version will be removed, and the final version will appear in the associated published volumes/issues of the publication. The date the article was first made available online will be carried over.